Beyond GDP: Tracking and Evaluating National Contributions to Social and Environmental Sustainability - Robert Picciotto (The Evaluation Center at Western Michigan University, 2021)
Background: The Gross Domestic Product (GDP) emerged as a convenient measure of national economic activity during the Great Depression. It was subsequently adopted by international development economists to track developing countries' progress so that, despite its severe deficiencies, it became 'locked in' by habit, convenience, and policy makers' preferences. Purpose: This article conceives of GDP as a social intervention fit for evaluation. It shows that the GDP has had a pervasive and pernicious influence on policy making. Since past strategies aimed at dethroning the GDP have failed, it proposes new, evaluator-driven approaches designed to undermine the GDP's dominance in the global market economy. Setting: The Stiglitz report commissioned in the wake of the 2008 financial crisis launched a 'Beyond GDP' movement. Since then, public alarm about the GDP growth addiction has escalated: the drawbacks of GDP as a free-market policy tool have become self-evident as the rich get richer, the ranks of the poor swell and the future of the planet hangs in the balance. Research Design: Not applicable. Data Collection and Analysis: For the twenty largest economies in the world, the article estimates climate change discounts to the GDP based on official CO2 emissions statistics and a social cost of carbon estimate derived from a 2015 survey of eminent climatologists. It also draws on composite indexes generated by four reputable social research organizations to rank countries for their contributions to the 5 Ps of the Sustainable Development Goals (SDGs): people, planet, prosperity, peace, and partnership. Findings: Pending the results of on-going efforts to upgrade worldwide statistics focused on the 169 SDG targets, the proposed GDP discounts help track progress towards the SDGs. But monitoring is not enough. In a policy world dominated by vested interests, the new 'Beyond GDP' indicators should be combined with principled, evaluator-directed evaluations. Keywords: Beyond GDP; climate change; evaluator-directed evaluation; Gross Domestic Product; indicators; Sustainable Development Goals